Mapping the landscape of research on the Regional Comprehensive Economic Partnership: based on CITESPACE and the TCCM framework - Li, Lijun (Bibliotecas. Anales de investigación, 2025)
Objective: This study examines the focus areas and patterns in the Regional Comprehensive Economic Partnership (RCEP) in the Web of Science database. CiteSpace was used to analyze the focal points of RCEP research in Web of Science. The researcher then employed the theory-context-characteristics-methodology (TCCM) framework to investigate potential avenues for future RCEP research. Methodology: This study uses a scientific information map based on journal articles and the topic "The Regional Comprehensive Economic Partnership" or "RCEP." According to Web of Science, between 2013 and June 18, 2023, 126 articles were published with journal article categories (including early access). Results and Discussion: The study uses CiteSpace to finalize the analysis of the focal points. Theresearcheremploysthetheory-context-characteristics-methodology (TCCM) framework to examine future trends in RCEP research. Seven findings are identified. Conclusions: The findings of this study include: 1. the identification of RCEP hotspots using co-author, co -institutions and keyword co-occurrence; 2. future trends identified by the TCCM framework for the study of RCEP. Contribution: This study identifies a bibliometric measure of current topics in RCEP using CiteSpace and the TCCM framework. These findings can offer research centers, libraries, and librarians recommendations and guidance for the management and classification of future RCEP studies.